Developing a Process-Based Learning Module to Enhance Writing Competence in Journalism Education - Mustaqim, Ahmad; Nurbaya, St; Mulyani, Mimi; Mazid, Sukron; Islahudin, Islahudin (Jurnal Pendidikan Progresif, 2025)
Developing a Process-Based Learning Module to Enhance Writing Competence in Journalism Education. Learning to write news texts for journalism concentration students still faces obstacles, so it is necessary to develop teaching materials in the form of modules that can help students master news text writing skills in a more targeted manner. This study aims to develop a news text writing module based on a process approach to improve writing skills in a directed manner. The method used is research and development (R&D), encompassing the stages of needs analysis, module design, expert validation, and student trials. This study involved five experts and 74 students from five universities in Yogyakarta. Based on the assessment results by material expert I, it obtained a score of 4.63 and was categorized as very good; material expert II obtained a score of 3.97 and was categorized as good. Furthermore, the assessment by graphic experts yielded a score of 4.12 (good), by linguistic experts a score of 4.08 (good), and by learning strategy experts a score of 4.6 (very good). The effectiveness test yielded a p-value of 0.000, indicating that the module is effective in improving the students’ ability to write news texts. The novelty of this research lies in integrating the process approach with the typical journalistic language guide in the form of a systematic module, which has not been developed specifically for journalism concentration students. Therefore, the use of news text writing modules based on a process approach is suitable as teaching material because it guides students through every stage of writing, from drafting to editing, provides linguistic support across a variety of journalism, and has a positive impact on writing skills and learning effectiveness. Keywords: learning modules, writing competence, news text, process approach.